1985
DOI: 10.1152/jappl.1985.58.5.1669
|View full text |Cite
|
Sign up to set email alerts
|

Bone and muscle atrophy with suspension of the rat

Abstract: A modification of the Morey tail suspension model was used to determine atrophic responses of rat bone and muscle with 14-90 days unloading of the hindlimbs. Bone uptake of methylene diphosphonate followed a phasic pattern similar to changes in bone formation rate in immobilized dogs and rats. Increased uptake at 60 days (P = 0.01, femur) indicated an increased bone metabolism. Regional densitometry demonstrated a preferential loss of bone mineral in the trabecular mass (P = 0.02) at 30 days and in the cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
24
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(33 citation statements)
references
References 0 publications
8
24
0
1
Order By: Relevance
“…The immobilization-induced loss of rectus femoris muscle mass after 4 weeks was 61% in the present study, which is comparable to a loss of soleus muscle mass of 50% after 30 days of tail suspension observed by LeBlanc et al [50]. The loss of CSA of individual striated muscle cells followed the same overall temporal pattern as muscle mass and muscle CSA.…”
Section: Discussionsupporting
confidence: 87%
“…The immobilization-induced loss of rectus femoris muscle mass after 4 weeks was 61% in the present study, which is comparable to a loss of soleus muscle mass of 50% after 30 days of tail suspension observed by LeBlanc et al [50]. The loss of CSA of individual striated muscle cells followed the same overall temporal pattern as muscle mass and muscle CSA.…”
Section: Discussionsupporting
confidence: 87%
“…Definitions as in Table 1 (Schellock et al 1985). We can hypothesize that maintaining approximately 45°o f suspension, as in the present experiment, enhanced the alterations previously reported in hindlimb muscle blood flow (LeBlanc et al 1985). An additional hypothesis to explain HS-induced muscle damage could be the reduced working length of the SOL muscle, and phasic contractions without load (See Riley et al 1990;Sancesario et al 1992) Whether maintaining HS rats at 45°tilt increased the angle of the ankle joint, and decreased the working range of the SOL muscle remains to be elucidated.…”
Section: Discussionsupporting
confidence: 86%
“…LeBlanc et al (1985) have suggested a decline in aerobic metabolism after HDS and hence changes in the contractile properties of the soleus muscle ®bre, the muscle continuing to contract but probably at an altered rate in response to the modi®ed functional requirements. McDonald et al (1992b), have also shown that the atrophied soleus muscle was more prone to fatigue, with a corresponding decrease in the release of vasodilatory metabolites (McDonald et al 1992a).…”
Section: Discussionmentioning
confidence: 99%
“…A reference blood sample was withdrawn via the femoral catheter (0.6 ml á min A1 ), a few seconds prior to microsphere injection and continued for 2 min after microsphere injection. The total infused radioactivity was obtained by comparison with a standard prepared at the time of injection (LeBlanc et al 1985).…”
Section: Infusion Of Microspheresmentioning
confidence: 99%
See 1 more Smart Citation